Screening of 'Y' chromosome microdeletions in Iranian infertile males - Ali Mohammad Malekasgar; Hayat Mombaini (Wolters Kluwer Medknow Publications, 2008)
Background : It has been hypothesized that microdeletions of Yq may account for a significant proportion of men with infertility. Three nonoverlapping regions, referred to as "azoospermia factors" (AZFa, b, c from proximal to distal Yq) have been defined as spermatogenesis loci and deletions in these regions have been shown to be pathogenically involved in male infertility associated with azoospermia or severe oligospermia. Aims: Evaluation the frequency of Y chromosome microdeletions in Iranian population. Materials and Methods: Fifty infertile men were selected. Semen analysis was done and on the basis of the mean sperm count, all patients were categorized into azoospermia and oligozoospermia, groups. Blood samples were obtained for DNA extraction and chromosomal analysis. Genomic DNA was extracted from blood lymphocytes and amplified by sequence tagged sites-polymerase chain reaction (STS-PCR) method to determine the presence of microdeletions in AZF locus. A total of 34 STS primers including two controls were selected to identify microdeletions of Y chromosome on each subject. Results and Conclusion: 26/50 cases (52%) showed deletion of at least one of the STS Marker. Totally 41 microdeletions was observed. A total of 17 cases (34%) had deletion in one STS. Four oligospermia cases (8%) had deletion in 2 STS site. Three azoospermia cases (6%) had again deletion in 2 STS site, but in different STSs. One case had three deletions in three STS site and finally one individual had seven deletions in AZF locus. The overall frequency of Y chromosome microdeletions observed in the present study was found to be 26/50 (52%). Comparison of our data with the result of other investigators world wide shows that the incidence of Yq microdeletions in Iranian population is much higher than international frequency. Our data agree with other studies regarding microdeletions of AZFc, but for microdeletions of AZFa (14.6%) our results is much higher and differ significantly with many studies.